The isolation and characterisation of Caulobacter from Manawatu water systems : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Microbiology at Massey University - Fenton, Christine Dunnington (Massey University, 1994)
This study reports the isolation of 22 strains of Caulobacter from a variety of local water supplies. Most of the strains (17) were from the sewage treatment plant, while others were isolated from rivers (2), tap water (1) and stored water (2). Conjugative plasmid transfer was demonstrated between a strain of E. coli and a sewage Caulobacter strain. Eckhardt gel analysis and antibiotic sensitivity tests confirmed that the transconjugant Caulobacter carried a plasmid conferring neomycin resistance when compared to the neomycin sensitive parent. Caulobacter isolated from sewage tended to carry more plasmids than freshwater Caulobacter, and showed an increase in resistance to many second generation antibiotics when compared to their freshwater counterparts. Based on the sequence of a 260 bp fragment of 16S rDNA. the identities of the Caulobacter isolates were confirmed. A phylogenetic tree constructed from the sequence data showed that the Caulobacter isolates form a diverse group. Some of the isolates appear to be closely related to marine Caulobacter and were able to grow in media containing 2.5% salt. Other isolates appear to be closely related to Pseudomonas diminuta. A number of new Caulobacter strains were identifed on the basis of their 16S rDNA sequences. The role of Caulobacter in the environment has not been well studied, partly due to the difficulties in detecting their presence. The use of the polymerase chain reaction to amplify the 16S rDNA sequence may help to overcome this problem, bearing in mind the diverse nature of the Caulobacter group.
Keywords: New Zealand Manawatu; Freshwater microbiology; Caulobacter